Peculiarities of the distribution of surface sediments of the Barents Sea eastern part. - Pavlidis, Yury A (PANGAEA, 1996)
Based on materials on geomorphology, hydrology, lithology, and sedimentation dynamics obtained during cruises of the P.P. Shirshov Institute of Oceanology in the Barents Sea, the author prepared a number of charts on content of the main particle size facies in shelf surface sediments, as well as a chart of lithologic types of sediments in the Barents Sea. Factors of sedimentation control and basic features of distribution of sedimentary material over its bottom area are taken into consideration.
(Table 1) Grain size composition of recent sediments from the eastern Barents Sea shelf
Keywords: Archive of Ocean Data; ARCOD; Arctic; Barents Sea; DEPTH, sediment/rock; GC; Grab; GRAB; Grain size analysis after Petelin (1967, Nauka, Moscow); Gravity corer; Professor Shtokman; PS-12; PS-913; PS-917; PS-918; PSh12; PSh12-1265; PSh12-1268; PSh12-1273; PSh12-1281; PSh12-1288; PSh12-1289; PSh12-1292; PSh12-1294; PSh12-1300; PSh12-1301; PSh12-1310; PSh12-1316; PSh12-1318; PSh12-1322; PSh12-1323; PSh12-1324; PSh12-1325; PSh12-1326; PSh12-1333; PSh12-1336; PSh12-1343; PSh12-1370; PSh12-1412; PSh12-1414; PSh12-1415; PSh12-1417; Size fraction < 0.001 mm, clay; Size fraction > 1 mm, gravel; Size fraction 0.005-0.001 mm; Size fraction 0.010-0.005 mm; Size fraction 0.050-0.010 mm; Size fraction 0.100-0.050 mm; Size fraction 0.250-0.100 mm; Size fraction 0.500-0.250 mm, 1.0-2.0 phi, medium sand; Size fraction 1.000-0.500 mm, 0.0-1.0 phi, coarse sand; Sum